THE GREEN BOND AS A PROSPECTIVE INSTRUMENT OF THE GLOBAL DEBT MARKET - Laskowska, Anna (Copernican Journal of Finance & Accounting, 2018)
Green debt is viewed as one of the youngest segments on the global financial market. Green bonds were defined as fixed-income securities, issued in order to obtain the capital for further financing or refinancing of undertakings contributing to the improvement of natural environment. In other words, to develop economy which is low-carbon and resistant to climate changes. They are relatively recent instruments, which have quickly become a substantial part of the dynamic ecological trend on the financial market. The research objective of the article is to identify the factors determining the development of the green bonds market. It is reasonable to systematize the stimuli of the evolution of this process, as the green bonds potential has not been fully utilized yet. Research methods applied were: critical analysis of the subject literature as well as reports on green bonds, data analysis from international ecological financial market, inductive method and the author’s own didactical material containing the case studies of five selected issuances of green bonds. The studies on subject literature were supplemented by an in-depth observation of how dynamically the green bonds market was developing in years 2012–2017. The outcome of the research: basic determinants of ecological bonds refer to demand, supply as well as realities and predictions regarding the functioning of the market. The research process confirmed that green bonds constitute a prospective dimension of the global debt market. It should be underlined, however, that if the environmental bonds segment is to develop rapidly, it is necessary to remove any barriers hindering its advancement, including low ecological awareness among the society or, in some cases, the country’s passivity towards pro-environmental policies.